Changes in food consumption expenditure in Malaysia - Ishida, Akira; Law, Siong Hook; Aita, Yoshihisa (Wiley Periodicals, 2003)
In rapidly developing Asian countries, food consumption has drastically expanded and diversified. Trends in Malaysian food consumption are typical of those of developing countries. The overriding objective of this article, therefore, was to explore the structural changes in food consumption expenditure in West Malaysia after the early 1970s when its food consumption diversified under rapid economic growth and urbanization. We have estimated Engel's expenditure elasticities for food items using aggregated cross‐sectional data from the Household Expenditure Survey. Our estimated results clearly indicate that while the expenditure elasticities of away‐from‐home food, and the elasticities of at‐home expenditures for meat, fruits and vegetables, milk and dairy products are relatively high, those of rice and sugar are low. This suggests that the food expenditure structure in West Malaysia has diversified, adding meat, fruits and vegetables, milk and dairy products to the most dominant food item, rice. Moreover, it is likely that the share of food away from home will increase with income enhancement and urbanization due mainly to economic growth.